(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the role of English in vocational education, particularly in the context of teaching English to Uzbek-speaking students. In modern professional education, English is not only an academic subject but also a practical tool for communication, employment, technological literacy, and access to international professional knowledge. The article discusses the importance of English for vocational learners, the specific needs of Uzbek-speaking groups, and effective approaches to teaching English for professional purposes. Special attention is given to communicative competence, English for Specific Purposes, digital learning resources, and the integration of language learning with professional disciplines. The study concludes that English language instruction in vocational education should be practice oriented, profession-based, and connected with students’ future careers.